PENGGUNAAN MODEL PEMBELAJARAN PORTOFOLIO DALAM UPAYA MENUMBUHKAN KREATIVITAS PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN KELAS IX B SMPN 12 BANDAR LAMPUNG - Sadanah, Sadanah (Lentera: Jurnal Ilmiah Kependidikan, 2015)
Civic education is a subject that focuses on the formation of themselves as citizens who are intelligent, skilled, and character. An educator should seek and use the learning model that can foster the creativity of learners and be able to build itself into a creative learners, and therefore in need pemebelajaran models that can foster the creativity of learners.In an effort to foster the creativity of learners, the researchers conducted a study class action. Of the many existing learning model learning model portfolio is a model appropriate learning in an effort to foster the creativity of learners. This is evident in the increase in the creativity of the participants in each cycle. In the first cycle, students who have creativity as much as 20 or 59%. Cycle II students who have creativity as much as 24 or 71%. Cycle III students use creativity as many as 29 people or as much as 85%, the third cycle of growth creativity of learners have achieved the expected indicators ie â‰¥ 75%. The results showed that the use of the learning model portfolio to foster the creativity of learners.